1978
DOI: 10.1128/jb.136.3.1027-1036.1978
|View full text |Cite
|
Sign up to set email alerts
|

Physiological role and membrane lipid modulation of the membrane-bound (Mg2+, na+)-adenosine triphosphatase activity in Acholeplasma laidlawii

Abstract: The membrane-bound adenosine triphosphatase (ATPase) activity of Acholeplasma laidlawii B differs in many respects from the common (Mg2+, Ca2+)-ATPase activity of higher bacteria, most notably in that it is specifically activated by Mg2+ and strongly and specifically stimulated by Na+ (or Li+). Various inhibitors diminish the ATPase activity with a concentration dependence which suggests that a single enzyme species is responsible for all of the observed ATP hydrolytic activity (both basal and Na+ stimulated).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1980
1980
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Although most of the bacterial ATPases resemble the proton-translocating ATPases of mitochondria and chloroplasts (5), ATPase of A. laidlawii is quite different. Jinks et al (6) have found that this enzyme is stimulated fourfold by Na+ but unaffected by K+ or by ouabain. It cannot be removed from the membrane by low ionic buffers or EDTA and is less sensitive to DCCD than bacterial ATPases.…”
Section: Discussionmentioning
confidence: 97%
“…Although most of the bacterial ATPases resemble the proton-translocating ATPases of mitochondria and chloroplasts (5), ATPase of A. laidlawii is quite different. Jinks et al (6) have found that this enzyme is stimulated fourfold by Na+ but unaffected by K+ or by ouabain. It cannot be removed from the membrane by low ionic buffers or EDTA and is less sensitive to DCCD than bacterial ATPases.…”
Section: Discussionmentioning
confidence: 97%
“…The absence of Na+ or K+ stimulation of the ATPase in vitro (13) argues against the existence of an ATP-driven Na+ (or K+ or both) pump in M. gallisepticum. Jinks et al (8), on the other hand, reported a fourfold stimulation of the membrane ATPase of A. laidlawii by Na+ and postulated that this enzyme functioned as an Na+ pump. Benyoucef et al (4) reported K+ stimulation of Na+ extrusion in M. mycoides var.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the inward diffusion of NaCl and water as a result of colloidosmotic and Donnan forces caused by intracellular nondiffusable macromolecules (11,14,22). The two bacteria without cell walls in which this phenomenon has been documented are Acholeplasma laidlawii (8) and Mycoplasma gallisepticum (12,17). Both species are known to be able to maintain their volume in the presence of glucose by an energy-dependent extrusion of NaCl and water from the cell.…”
mentioning
confidence: 99%
“…An Na ϩ -translocating ATPase, recently discovered in the thermophilic Clostridium fervidus (237), is very likely to be of the vacuolar type as judged by the enzymatic and biochemical properties of the purified enzyme (97). Furthermore, the enzymatic features of an Na ϩ -stimulated-ATPase observed in Mycoplasma mycoides (a parasitic glycolytic organism) are virtually identical to those of the E. hirae enzyme (25), and an Na ϩ -stimulated ATPase from Acholeplasma laidlawii seems to be of the V type as judged by its subunit composition (104,159).…”
Section: Sodium Transport Systemsmentioning
confidence: 99%